Female murderers in a southern city, 1975–1992 - Johnson, Ida M. (American journal of criminal justice, 1996)
A study of a population of 36 females arrested for homicide in a southern, nonurban city from 1975 to 1992 was conducted using both qualitative and quantitative data. The study explored the demographic, social, legal, and offense characteristics of female homicide offenders as well as events leading to the murder. The profile of female homicide offenders in a southern, non-urban setting that emerged from this study is supportive of earlier studies focusing on female homicide offenders in large urban areas.